Gain-Sharing in outsourcing relationships: A proposed model - Reinaldo Guerreiroa; Surendra Agrawal; Carlos Alberto Pereiraa (Journal of Accounting, Business and Management (JABM), 2005)
This study is concerned with the outsourcing relationship between business providers and business customers of information technology services. Companies usually adopt one of three methods in determining the price of outsourced services: fixed price, cost-plus or gain-sharing. Gain-sharing arrangement is quite popular, but is difficult to negotiate and monitor. Such a contract requires measurement of gains and their allocation among the two parties. The present paper proposes a model of gain-sharing which is based on the principles of activity-based costing (ABC). The motivation for the development of this model comes from a case study in which the problem of gain-sharing emerges in the relationship between two large-scale international companies that operate in Brazil. The model proposed in this paper would divide activities and their costs in several categories using the principles of ABC, particularly unit level, batch level and product level. The total contract cost would include some planned unused capacity to provide for fluctuations in the demand of service by the service receiver. A gain may arise for two reasons: (a) a reduction in the cost of unused capacity because of an increase in the total service demanded by the service receiver; and (b) a reduction in the costs actually incurred by service provider. The outsourcing contract should provide for an allocation of these gains among the two parties. It is suggested that for (a) a major part should be allocated to the service receiver, while for (b) a major part should go to the service provider. The adoption of the proposed model should lead to an arrangement that is considered to be more satisfactory by both parties. It is expected to provide more accurate estimation and computation of costs at various volume levels, and to a more transparent allocation of any gains. The service provider will also get some guidance with respect to resources that it should earmark for the contract. It is hoped that the model would be carefully examined by academicians and would be considered by companies when entering into an outsourcing contract.